2011
DOI: 10.1088/0953-8984/24/1/015702
|View full text |Cite
|
Sign up to set email alerts
|

Interatomic potential for uranium in a wide range of pressures and temperatures

Abstract: Using the force-matching method we develop an interatomic potential that allows us to study the structure and properties of α-U, γ-U and liquid uranium. The potential is fitted to the forces, energies and stresses obtained from ab initio calculations. The model gives a good comparison with the experimental and ab initio data for the lattice constants of α-U and γ-U, the elastic constants, the room-temperature isotherm, the normal density isochore, the bond-angle distribution functions and the vacancy formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 57 publications
6
55
0
1
Order By: Relevance
“…As we see the data from Fugure 4 the CMD melting curves at the pressures lower than 100 GPa are close to the results of experiment and similar to calculations [4] employing the coexistence method. It is worth noting that not only the points but the slopes of interpolated curves for experimental and calculated with new EAM data are in good agreement.…”
Section: Melting Curvesupporting
confidence: 86%
See 3 more Smart Citations
“…As we see the data from Fugure 4 the CMD melting curves at the pressures lower than 100 GPa are close to the results of experiment and similar to calculations [4] employing the coexistence method. It is worth noting that not only the points but the slopes of interpolated curves for experimental and calculated with new EAM data are in good agreement.…”
Section: Melting Curvesupporting
confidence: 86%
“…In the case of CMD calculations, embedded atom method (EAM) [8] or modified EAM [18] are used to develop interatomic potential based on ab initio calculated data. Considering solid-liquid transition, Smirnova et al [4] have found that the obtained melting curve of γ uranium is close to the DAC experimental data, but only up to 50 GPa.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Атомні маси умовно дорівнюють А1 = 240, А2 = 150, А3 = 28. Значення параметрів потенціалу для взаємодії атомів з вказаними атомами взяті з [10][11][12][13]. Параметри різнорідних атомів були визначені як середні для кожної пари атомів:…”
Section: конструювання модельного кристалаunclassified